Constraint Analysis National Health Insurance - Evriany, Nurul; Favian, Rhesa Milzam; Rochmah, Thinni Nurul; Ernawaty, Ernawaty (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Introduction: The government ratifies and establishes the Healthcare and Social Security Agency that manages health insurance for all people in Indonesia. However, this agency, through the National Health Insurance program, can still not pay all claims submitted by hospitals. Several claims were rejected because the claimant did not meet the requirements for the benefits covered. This research analyzes national health insurance claims' constraints to reduce unworthy claims at Undata Hospital, Central Sulawesi Province. Method: This research is a Constraint Analysis with an analytical observational method and a cross-sectional approach where the researcher wants to identify constraints in each BPJS claim flow process, which consists of verification, data coding process, and file entry process at the National Health Insurance Unit of Undata Hospital, Central Sulawesi Province. This research was conducted from November 2020 to September 2021. There were 17 subjects in this study. Sampling using a purposive sampling technique. Results: The cause of the constraint in the BPJS Health verification claim process at Undata Hospital is that the health service verification process was not carried out before being it to Agency. The cause of the constraint in coding BPJS Health claim files at Undata Hospital is that, based on knowledge constraints, it is known that there is no training for coders regarding the coding process. Conclusion: Implementing the BPJS Health claim procedure at Undata Regional Hospital, Central Sulawesi Province, still needs improvement because the existing SOP still lacks a detailed explanation of the stages of the existing claim procedure.Keywords: Constraints, Health Guarantee, Claims